Pengaruh ekstrak teh hijau (Camellia sinensis) terhadap kadar malondialdehid (MDA) plasma dan kekuatan genggam tangan lanjut usia - Fera Nofiartika; Susetyowati Susetyowati; I Dewa Putu Pramantara; Lily Arsanti Lestari (Jurnal Gizi Klinik Indonesia, 2016)
Background: Prevalence of Indonesian elderly has now reached 7%, which is considerably high. Physical performance is an important health status indicator in elderly. Declining of physical performance such as hand grip strength in elderly is related to oxidative stress. Furthermore, oxidative stress plays an important role on the decreasing of skeletal muscle function. Plasma malondialdehyde (MDA) is a lipid peroxidation residue that is often used as an oxidative stress biomarker. Meanwhile, tea is the most widely drunk beverage after water. Green tea contains antioxidants that can reduce the damages caused by oxidative stress. Objective: To assess the effect of green tea extract (GTE) on plasma malondialdehyde level and hand grip strength of elderly.Method: This was a double-blind experimental with pre-post test and control group. Fifty-seven elderly people from Balai Pelayanan Social Tresna Wredha (BPSTW) Abiyoso and Budi Luhur who met inclusion and exclusion criteria were divided into 2 groups. During 30 days, the first group was given 2 capsules of GTE a day (±168 mg catechin and 95 mg Epigallocatechin gallate (EGCG) and the second group was given a placebo. MDA was measured by thiobarbituric acid  (TBA)method and hand grip strength was measured by handgrip hand grip dynamometer. Results: There was a significant decreasing MDA (p<0,05) in the GTE group, but not in the placebo group. There was also increasing handgrip strength in the GTE group but not in the placebo group. Conclusion: Green tea extract can prevent increasing MDA and declining physical handgrip strength in elderly.